2022
DOI: 10.2188/jea.je20210277
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Epidemiological Survey of Adolescent Patients With Diverse Symptoms Similar to Those Following Human Papillomavirus Vaccination: Background Prevalence and Incidence for Considering Vaccine Safety in Japan

Abstract: Background Since June 2013, Japan has suspended proactive recommendation of human papillomavirus (HPV) vaccination due to self-reported diverse symptoms, including pain and motor dysfunction, as possible serious adverse events following immunization. Although these symptoms may be seen in adolescents without HPV vaccination, their frequency, taking into account disease severity, has not been examined. Methods A two-stage, descriptive, nationwide epidemiological survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Consequently, the MHLW's Adverse Effects Review Committee confirmed that the various symptoms reported after vaccination were functional physical symptoms [23,24]. A nationwide epidemiological survey conducted by the Sobue Group of the MHLW reported that a few symptoms similar to those reported as post-vaccination symptoms existed among people without a history of HPV vaccination [25]. In a questionnaire survey of women born between 1994 and 2000 in Nagoya, there was no significant difference in the age-adjusted incidence of 24 symptoms between vaccinated and unvaccinated women and no evidence of a causal relationship between the symptoms and HPV vaccination [26].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the MHLW's Adverse Effects Review Committee confirmed that the various symptoms reported after vaccination were functional physical symptoms [23,24]. A nationwide epidemiological survey conducted by the Sobue Group of the MHLW reported that a few symptoms similar to those reported as post-vaccination symptoms existed among people without a history of HPV vaccination [25]. In a questionnaire survey of women born between 1994 and 2000 in Nagoya, there was no significant difference in the age-adjusted incidence of 24 symptoms between vaccinated and unvaccinated women and no evidence of a causal relationship between the symptoms and HPV vaccination [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the estimated case-fatality ratio of COVID-19 infection ranges from 0.001 % (5–9 years old) to 8.29 % (>80 years old) [20] . The efficacy of HPV and COVID-19 vaccines is as high as 95 % or more, and their relative safety is also high [21] , [22] , [23] . Nevertheless, our survey found that people were more afraid of a COVID-19 infection than an HPV infection and more willing to inoculate their children with the COVID-19 vaccine than with the HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In June 2013—7 years after the first licensed vaccine for the prevention of cervical cancer and other diseases caused by human papillomavirus (HPV) 7–10 —concerns about a potential link between HPV vaccination and self-reported CRPS stemming from case reports in the media led to the suspension of the HPV vaccination program in Japan 11–13 ; this suspension was not lifted until November 2021. 14–16 In 2015 and again in 2017, in analyses of data from over 270 million doses of HPV vaccines administered in multiple countries, the Global Advisory Committee on Vaccine Safety found no causal association between HPV vaccination and a range of symptoms and diagnoses that included chronic pain, motor dysfunction, CRPS, and postural tachycardia syndrome.…”
Section: Introductionmentioning
confidence: 99%